2017
DOI: 10.1371/journal.pntd.0005772
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis and HIV/AIDS in Brazil: Are we aware enough?

Abstract: BackgroundThe urbanization of visceral leishmaniasis (VL) and the concurrent movement of the HIV infection to rural areas in Brazil are possible mechanisms associated with an increased number of Leishmania/HIV coinfected people. This study aimed to describe the clinical and epidemiological profile of VL/HIV coinfected patients and compare this profile to non-coinfected VL patients.MethodsCases of VL/HIV coinfection were obtained through a probabilistic record linkage of databases of VL and AIDS cases from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
36
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 18 publications
(27 reference statements)
4
36
1
2
Order By: Relevance
“…Mortality due to leishmaniasis is considered to be potentially avoidable and is generally associated with malnutrition, late diagnosis, and HIV infection. Individuals with VL/HIV coinfection are three times more likely to die than the general population, and the lethality rate may reach 25% in coinfected individuals 5 . However, at the community level, other factors may be associated with the high disease burden and culminate in deaths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality due to leishmaniasis is considered to be potentially avoidable and is generally associated with malnutrition, late diagnosis, and HIV infection. Individuals with VL/HIV coinfection are three times more likely to die than the general population, and the lethality rate may reach 25% in coinfected individuals 5 . However, at the community level, other factors may be associated with the high disease burden and culminate in deaths.…”
mentioning
confidence: 99%
“…Another important factor for the stable or even increasing trend of leishmaniasis mortality is the geographical overlap of leishmaniasis with major areas of HIV transmission 15 , since patients coinfected with HIV are at higher risk of death than non-coinfected patients 3,5 . Research conducted in Minas Gerais showed that the lethality due to leishmaniasis was 1.9 higher in HIV+ individuals, with an odds ratio (OR) of 10.9 and an unfavorable outcome up to 6 months after diagnosis 15 .…”
mentioning
confidence: 99%
“…in a large portion of co-infected patients at the time of VL diagnosis 284[23,34,35,37,38]. However, we emphasize that the diagnosis of HIV having been 285 performed before VL in most co-infected patients, these patients should be 286 immunologically less suppressed since they would be taking antiretroviral, but most of 287 19 them had a viral load above 50 copies.…”
mentioning
confidence: 89%
“…In the past two decades, Brazil witnessed changes in the epidemiology of VL, which moved from a rural endemic in poorest Northeastern States to an urban emerging disease spreading into the more developed Southeastern Region (Conti et al, 2016;Martins-Melo et al, 2018). In this new setting, the epidemics of VL and AIDS intertwined (Lindoso et al, 2014;Leite de Sousa-Gomes et al, 2017;Lindoso et al, 2018). Governmental guidelines for the therapy of VL and VL-HIV coinfection were expedited, but data concerning their efficacy are still limited (de Melo and Fortaleza, 2013).…”
Section: Introductionmentioning
confidence: 99%